2013
DOI: 10.1080/07373937.2013.811592
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature, Air Velocity, and Ultrasound Application on Drying Kinetics of Grape Seeds

Abstract: The objective of this study was to determine the influence of temperature, air velocity and ultrasound application on the drying kinetics of grape seeds. The drying kinetics were determined at 1.0, 1.5, 2.0 and 3.0 m/s and at 40, 50, 60 and 70ºC. At 1.0 and 1.5 m/s, the experiments were carried out with and without ultrasound application. To establish the influence of the variables on the drying kinetics, the results were modeled by means of both the Peleg and a diffusion model. The activation energy was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…It was observed that increasing of drying temperature and ultrasonic duration led to increasing of the D eff due to more rapid loss of water in the higher temperature and as a result of ultrasound pretreatment. This is consistent with reported results by Clemente, Sanjuán, Cárcel, and Mulet (). The D eff values are in agreement with the documented values of 5.84 × 10 −9 to 7.36 × 10 −9 m 2 /s for drying of mirabelle plum in ultrasound‐assisted osmotic at ultra‐sonication time at two levels (10 and 30 min) (Dehghannya et al, ), 0.82 to 4.32 × 10 −10 m 2 /s for Andean blackberry in ultrasound as a pretreatment for convective dryer at time of sonication (10–30 min) and air temperature (40–60 °C) (Romero & Yépez, ), 0.763 × 10 −10 to 2.29 × 10 −10 m 2 /s for strawberry in ultrasound application under the convective drying at acoustic power (0, 30, and 60 W) and the air temperature (40, 50, 60, and 70 °C) (Gamboa‐Santos et al, ), the values of D eff the of button mushroom slices varied in the range of 2.93 × 10 −9 to 5.46 × 10 −9 (m 2 /s) during ultrasound as a pretreatment and infrared drying process, and D eff varied in the range of 3.85 × 10 −9 to 6.32 × 10 −9 (m 2 /s) during ultrasound as a pretreatment under hot air drying process (Zhang et al, ).…”
Section: Resultssupporting
confidence: 94%
“…It was observed that increasing of drying temperature and ultrasonic duration led to increasing of the D eff due to more rapid loss of water in the higher temperature and as a result of ultrasound pretreatment. This is consistent with reported results by Clemente, Sanjuán, Cárcel, and Mulet (). The D eff values are in agreement with the documented values of 5.84 × 10 −9 to 7.36 × 10 −9 m 2 /s for drying of mirabelle plum in ultrasound‐assisted osmotic at ultra‐sonication time at two levels (10 and 30 min) (Dehghannya et al, ), 0.82 to 4.32 × 10 −10 m 2 /s for Andean blackberry in ultrasound as a pretreatment for convective dryer at time of sonication (10–30 min) and air temperature (40–60 °C) (Romero & Yépez, ), 0.763 × 10 −10 to 2.29 × 10 −10 m 2 /s for strawberry in ultrasound application under the convective drying at acoustic power (0, 30, and 60 W) and the air temperature (40, 50, 60, and 70 °C) (Gamboa‐Santos et al, ), the values of D eff the of button mushroom slices varied in the range of 2.93 × 10 −9 to 5.46 × 10 −9 (m 2 /s) during ultrasound as a pretreatment and infrared drying process, and D eff varied in the range of 3.85 × 10 −9 to 6.32 × 10 −9 (m 2 /s) during ultrasound as a pretreatment under hot air drying process (Zhang et al, ).…”
Section: Resultssupporting
confidence: 94%
“…It can be concluded that step-down relative humidity not only can improve drying efficient but also achieve a good product quality. Similar findings were reported by Chua et al [5] who found that applying variable drying conditions could reduce the color changes of potato, guava, and banana by 87%, 75%, and 67%, respectively.…”
Section: Color Measurementssupporting
confidence: 89%
“…[4] Currently, hot air drying is the mostly widely used method for vegetables and fruits drying. [5,6] In addition, the quality of dried vegetables and fruits are affected by drying parameters such as drying equipment configuration, drying media, temperature and the length of drying time. It was reported that higher drying temperature significantly accelerated deterioration of color attributes due to non-enzymatic browning reactions that increase the reddish and yellowish color of product as the drying temperature increased.…”
mentioning
confidence: 99%
“…The Arrhenius equation has been widely used as a model of temperature's effect on the rates of chemical reactions and biological processes in foods (e.g., Clemente et al, 2014;Labuza, 1984;Saguy et al, 2005;van Boekel, 2009). However, the applicability and usefulness of the Arrhenius equation to chemical reactions and biological processes in foods, especially solids, and the relevance of the statistical-mechanical assumptions on which it is based can be challenged on several grounds (Peleg et al, 2012).…”
Section: Modelingmentioning
confidence: 99%